Action presidents. #4, John F. Kennedy! - Van Lente, Fred (Van Lente, Fred. Action presidents, 2018)
Proffers a humorous graphic novel presenting historical stories about John F. Kennedy, such as the fact that he was chronically ill as a child, survived shark-infested waters, and sent a secret message through a coconut.